O abordare etnografică a experienţei copilăriei în Bucureştiul contemporan - Savu, Dumitru-Alin (Calitatea Vieții, 2017)
This article explores the experience of childhood among children from Bucharest enrolled in extracurricular activities. The first part of the article is a review of literature focusing on the three central pillars of the paper: first, how we define and understand children and childhood as objects of research; second, time and space as they are theorised in relation to the experience of childhood; third, the status of children statute as social actors, their connection to global phenomena and the implications of this connection on the way childhood is lived. The second part of the article uses four ethnographic data to illustrate the experience of these children’s lives. Moreover, I complement this step using details from the other respondents’ experiences – parents, educators, therapists – following the theoretical line defined in the first part of the article. Taking into consideration all these varied experiences, the article points out the agency of all the persons involved and argues that adults and children share and build together the world they live in. Thus, the experience of childhood becomes entangled in adults’ experience of work, as institutions apparently serving the child-rearing process also respond to the labour market need of more time from the parents.